The problem of proper nouns in the translation works of Cho'lpon, M.Shaykhzoda and J.Kamol (Zien Journal of Social Sciences and Humanities, 2023)
Although the history of translation in Uzbekistan has been around for thousands of years, our writers, who have been mentioned above and worked after the year 1917, have made this field to be peaked as a subject. The works of Famous classics and contemporary artists of Western Europe were translated into Uzbek. Uzbek readers have the privilege of reading the works of great writers and poets of Russia and Western Europe, including Shakespeare, Schiller, Goethe, Pushkin, Balzac, L. Tolstoy, and many others in their native languages.